Death Lore : Texas Rituals, Superstitions, and Legends of the Hereafter. - Untiedt, Kenneth L. (University of North Texas Press, 2010)
Examines the lore of death and whatever happens afterward. This work looks at places where people are buried, either permanently or temporarily. It also explores some of the stranger stories about what happens after we're gone, and offers some philosophical musings about death in general, as well as our connection to those who have gone before.